Green Ecology Questionnaire (GEQ) Based on Understanding of Cosmic Religious Environmental Law - Rahayu, Mella Ismelina Farma; Susanto, Anthon Freddy; Sudiro, Amad (Journal of Law and Legal Reform, 2025)
The current environment has been exploited without consideration or regard for sustainability and ecological balance. Forests have been plundered and burned, natural resources have been depleted without any effort to replenish them, and development in many cities has ignored spatial planning. All of these actions have ultimately resulted in severe environmental degradation. The decline in the carrying capacity and capacity of the environment, pollution and destruction of the environment, climate change, deforestation, and damage to terrestrial and marine ecosystems have become serious threats to the survival of humans and other living creatures. The issue examined in this paper is how to revive public understanding and awareness (participation) of the law in preserving the function of the environment. This paper uses a philosophical and legal hermeneutic approach, which is to look at the fundamental side using the method of text criticism, which refers to how the grand discourse on environmental law is criticized through several main references. Through this approach and method, it is hoped that the Green Ecology Quitionent (GEQ) model concept can be developed based on cosmic religious environmental law. Cosmic religion is a fundamental concept of diverse local wisdom possessed by Indonesian society. This model concept is expected to become a reference or starting point for the development of environmental policy, environmental education, law enforcement, management, and preservation of environmental functions in Indonesia.